Donor‐Specific Antibodies in Liver Transplantation - Nilles, Kathy M. (Clin Liver Dis (Hoboken), 2020)
http://aasldpubs.onlinelibrary.wiley.com/hub/journal/10.1002/(ISSN)2046-2484/video/15-1-reading-nilles a video presentation of this article Answer questions and earn https://www.wileyhealthlearning.com/Activity/7025330/disclaimerspopup.aspx